INFLUENCE OF THE THERMAL PROCESS STAGE ON THE SIZE OF VALID GRAIN OF CONSTRUCTIONAL CARBURIZED STEEL GRADE 20CHN3A - S. P. Rudenko; A. L. Valko; A. A. Shipko; A. N. Chichin (Литьë и металлургия, 2016)
Results of studies of the kinetics of changes in actual grains during technological process at different stages of the manufacture of parts with the use of a universal metallographic etchant to identify borders of valid grains in rolling and stamping in carburizing layers and core parts made of alloy structure steel grades are presented.